Pelatihan Komunikasi Verbal dan non verbal di SMA Swasta Bunga Bangsa - Nurul Saniah; Indah Lestari; Roibil Alwi (Indonesian Journal of Community Engagement, 2024)
Experts assess that communication is a very important need for a person in social life. Which encourages humans to communicate with other humans. Through communication, humans can find out what is happening around them, and with communication, humans can develop knowledge obtained from information about the surrounding environment. Communication does not only use words in delivery, but communication can also use sign language. In everyday life we often see people communicating using verbal and non-verbal communication. Verbal communication is communication that is conveyed using language both orally and in writing. Meanwhile, non-verbal communication is communication with signals such as body movements and facial expressions. Verbal and non-verbal communication can be used at the same time, because when we convey communication to other people using words and language we also use body language to further clarify what we are saying. This is different from communicating with people who cannot speak, we have to use sign language and body movements so that the person understands what we are demonstrating. For example, in special schools (SLB). On this occasion the author will carry out a presentation to the community with the theme "Verbal and non-verbal communication training at Bunga Bangsa Private High School. The aim of this community service is to understand the forms and functions of verbal and non-verbal communication.